2015
DOI: 10.3233/ch-151924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unidirectional flow shear stresses on the formation, fractal microstructure and rigidity of incipient whole blood clots and fibrin gels

Abstract: Incipient clot formation in whole blood and fibrin gels was studied by the rheometric techniques of controlled stress parallel superposition (CSPS) and small amplitude oscillatory shear (SAOS). The effects of unidirectional shear stress on incipient clot microstructure, formation kinetics and elasticity are reported in terms of the fractal dimension (df) of the fibrin network, the gel network formation time (TGP) and the shear elastic modulus, respectively. The results of this first haemorheological applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Based on viscoelastic properties of incipient blood clots, a new biomarker of healthy, bleeding or prothrombotic clot microstructure was proposed, named the fractal dimension, which has been shown to have clinically important correlations [31-33]. Clots derived from the blood of subjects with pulmonary embolism showed accelerated establishment of viscoelastic properties compared to healthy donors [34].…”
Section: Viscoelastic Properties Of Fibrin (Fibrin Rheology)mentioning
confidence: 99%
“…Based on viscoelastic properties of incipient blood clots, a new biomarker of healthy, bleeding or prothrombotic clot microstructure was proposed, named the fractal dimension, which has been shown to have clinically important correlations [31-33]. Clots derived from the blood of subjects with pulmonary embolism showed accelerated establishment of viscoelastic properties compared to healthy donors [34].…”
Section: Viscoelastic Properties Of Fibrin (Fibrin Rheology)mentioning
confidence: 99%
“…These changes were confirmed by increases in G`G P , a measure of functional clot properties including viscoelastic strength, polymerisation and crosslinking, following both submaximal exercise and maximal exercise, suggesting that the resulting clot has increased viscoelastic strength following both exercise intensities. We have previously reported that d f has accurately quantifies the effects of acute and chronic vascular inflammatory changes [21][22][23], sheer stress [29], temperature [25] and haemoconcentration/dilution [24] on clot structure, all of which are established to occur during high intensity exercise [1,2].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Increases in fibre thickness. Hints of β-sheet formation induced by flow can be seen in [269], while in a very striking study, Campbell et al [270] saw a huge increase in the flow-induced diameter of fibrin fibres, from a mean of 79 to 226nm.…”
Section: Effects Of Flow On Fibrin Propertiesmentioning
confidence: 99%